2012
DOI: 10.4172/1948-5956.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gene Expression Profiles between Human Breast Tissue and Peripheral Blood Samples for Breast Cancer Detection

Abstract: The purpose of this study is to check the similarities of differential gene expression of 11 genes in breast cancer tissue and blood samples from the same individual for early detection of breast cancer. We had investigated differential gene expression by qRT-PCR in 20 breast cancer patients' tumoral tissues and corresponding blood sample. In our analysis BRCA2, HER-2, ER, PR, MET and BRAF mRNA levels were significantly over expressed in tumoral tissues. ER and PR mRNA levels were not detected in any of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…All of the observations support the tumor suppressor role of BRCA1 gene in breast cancer development. The relatively increased BRCA1 expression in premenopausal patients in our study seems consistent with the findings of Kandula's and colleagues who showed an increase in BRCA1 expression in premenopausal women with grades II and III of breast cancer [38].…”
Section: Post-menopausesupporting
confidence: 93%
“…All of the observations support the tumor suppressor role of BRCA1 gene in breast cancer development. The relatively increased BRCA1 expression in premenopausal patients in our study seems consistent with the findings of Kandula's and colleagues who showed an increase in BRCA1 expression in premenopausal women with grades II and III of breast cancer [38].…”
Section: Post-menopausesupporting
confidence: 93%
“…In contrast, 26 articles reported sensitivity and specificity figures greater than 70% for combined biomarkers in the form of panels 27,29,30,61,76,77,81,82,87,90,93,94,97,98,101,104,106,111-114,118,123,124,132,147 leaving only 6 panels with figures lower than 70%. 61,76,93,114,124,132 Finally, 27 articles reported AUC and P values, 26,62,63,67,71,72,78,83,84,88,102,110,116,120,122,125,127,130,133,135,137,139,140,142,143,145,146 and of these, AUC was lower than 0.7 67,133,1...…”
Section: Discussionmentioning
confidence: 99%
“…The purpose and contribution of C 3 is justified based on the consideration of tissue-specific differences in the expression of genes, which have been established in biological studies even for same-condition (homogeneous) population (variability of expression within and across populations) [Kandula et al, 2012, Schobesberger et al, 2008, Radich et al, 2004, Shin et al, 2011. Basically, the inclusion of C 3 aims to alleviate cross-tissue differences appearing in the base populations of control breast and control blood engaged in our study.…”
Section: Rationale and Design Methodologymentioning
confidence: 99%